The Language Extended Lexicon, Revisited - Wehbe, Ricardo (2011)
We present in this paper some redefinitions of concepts already well-known in the literature about the Language Extended Lexicon (LEL), prompted by the medium-term objective of constructing a process to assist the user in the construction of LEL. The underlying idea is to look at LEL from a different perspective, rather as a mathematical object than as a Requirements Engineering methodology aimed at deriving scenarios. The main LEL concepts are presented after a review of some of the semiotics concepts that originally inspired it. We outline the main research lines, the problems we expect to encounter, and the approaches, mainly borrowed from the Data Mining area, by which we expect to tackle them.